Lessons from the Believing Game - Tim Doherty (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
My essay reflects on different lessons I have learned in using the believing game to promote deliberative dialogue in first-year writing courses. I have learned that it helps not to be in a hurry: spending enough preparation time with students thinking about belief itself, listening to students' stories and sense of attachment to beliefs, and playing the game repeatedly. I also explore the believing game as a mode of play, especially the fruitful way that role-play can be integrated into the believing game.